Innovations and Online Marketing Services Trends in Albanian Tourism Sector - Noti, Elton; Brunela Trebicka, Phd (European Journal of Multidisciplinary Studies, 2016)
Albania is a rich country with a lot of nature and cultural tourism resources situated in the in the Balkans region where there are much opportunities for developing different types of tourism. After a long period of transition, since the fall of the communist regime in 1990, the tourism industry began to be considered as one of the economic sectors with potential for development in the future. But, tourism enterprises had to be faced with a high competition from other countries in the region and a lack of experience in the field of tourism services. This study aims to identify the attitudes of senior management of tourism enterprises (Accommodation units, Travel Agencies and Restaurants) on the adoption of new services on the Internet, the use of ICT to sell the services offered and how much they were aware of the benefits that online marketing brought using their websites etc. To realize the aim, are raised the research questions and hypotheses. The research instrument used was a questionnaire. The sample consisted of N = 208 participants, representatives of tourism enterprises at five districts of Albania, respectively: Tirana, Durres, Shkodra, Vlore and Saranda .The results show that the entrepreneurs/managers make a very good job for the creation of new services via the Internet, also they support significantly the use of ICT-s to sell their services, they were aware of the benefits that brought a website to the marketing of tourism services and there was a great interest to learn more about the internet.